2005
DOI: 10.1051/0004-6361:20052739
|View full text |Cite
|
Sign up to set email alerts
|

QuantitativeHandKband spectroscopy of Galactic OB-stars at medium resolution

Abstract: Abstract. In this paper we have analyzed 25 Galactic O and early B-stars by means of H and K band spectroscopy, with the primary goal to investigate to what extent a lone near-IR spectroscopy is able to recover stellar and wind parameters derived in the optical. Most of the spectra have been taken with -, at an intermediate resolution of 12 000, and with a very high S/N, mostly on the order of 200 or better. In order to synthesize the strategic H/He lines, we have used our recent, line-blanketed vers… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
92
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(97 citation statements)
references
References 50 publications
5
92
0
Order By: Relevance
“…Here D(0.1) indicates that D is for the He/H = 0.1 abundance ratio. In this table we see that on average δD < 0 and that |δD| is larger the higher the He/H abundance ratio and for 19 000 < ∼ T eff < ∼ 23 000 K. In recent studies of supergiants Repolust et al (2005), Crowther et al (2006), Searle et al (2008), and Markova & Puls (2008) have found that an abundance He/H = 0.2 fits their atmospheres. From Table 9 we see that a ratio He/H = 0.2 effects the value of D by less than the error of measurement of D. Nevertheless, these differences are systematic and can be important for the hottest supergiants.…”
Section: Effects Related To the Rotationmentioning
confidence: 73%
“…Here D(0.1) indicates that D is for the He/H = 0.1 abundance ratio. In this table we see that on average δD < 0 and that |δD| is larger the higher the He/H abundance ratio and for 19 000 < ∼ T eff < ∼ 23 000 K. In recent studies of supergiants Repolust et al (2005), Crowther et al (2006), Searle et al (2008), and Markova & Puls (2008) have found that an abundance He/H = 0.2 fits their atmospheres. From Table 9 we see that a ratio He/H = 0.2 effects the value of D by less than the error of measurement of D. Nevertheless, these differences are systematic and can be important for the hottest supergiants.…”
Section: Effects Related To the Rotationmentioning
confidence: 73%
“…For this purpose, we used a grid of models for dwarfs and supergiants in the O and early B-star range, which has already been used in previous comparisons (Lenorzer et al 2004;Puls et al 2005;Repolust et al 2005). fastwind models have been calculated with three "explicit" atoms, H, He and our new N atom.…”
Section: Comparison With Results From Cmfgenmentioning
confidence: 99%
“…At least for HD 190429A, an independent re-analysis by Bouret et al (2005), by means of the alternative model-atmosphere code cmfgen (Hillier & Miller 1998), confirms the corresponding calibration. Finally, for HD 15570, we use parameters derived from H-and K-band spectroscopy by Repolust et al (2005).…”
Section: Stellar Sample and Observational Materialsmentioning
confidence: 99%